The enigma: Decision‐making to transfer residents to the emergency department; communication and care delivery between emergency department staff and residential aged care facilities' nurses. (20th February 2022) - Gurung, Apil; Romeo, Michele; Clark, Sean; Hocking, Julia; Dhollande, Shannon; Broadbent, Marc
Abstract: Objective: To investigate the experience of nurses involved in decision‐making to transfer residents from a residential aged care facility (RACF) to their local hospital emergency department. This paper reports on the findings of the second phase of a two‐phase study. Methods: Qualitative semi‐structured interviews with 19 aged care nurses were conducted. Interviews were audio‐taped and transcribed verbatim, and a thematic analysis was carried out. Results: The analysis revealed five major themes that influenced decision‐making in relation to the transfer of a resident from the residential aged care facility to the emergency department: conflict with key stakeholders; knowledge and experience; policy and process; stakeholder perception; and recognition and support. Conclusions: Robust outreach programs, support from other health‐care professionals, and improving interdisciplinary understanding and communication between aged care nurses, paramedics and the emergency department would be advantageous to ensure effective care delivery and decision‐making.